FORMULASI COLD CREAM PROPRANOLOL UNTUK PENGHANTARAN TRANSDERMAL DENGAN BASIS EMULSI YANG MENGANDUNG VCO (VIRGIN COCONUT OIL) - Lestari, Muji; Binarjo, Annas (Pharmaciana, 2013)
Propanolol is a non-selective beta-blocker that is used widely to overcome cardiovascular disorder.Development of propranolol in transdermal delivery is necessary to avoid the first pass metabolism that reducesthe active metabolite up to 15-23% left. This study was objected to determine the effect of VCO (Virgin CoconutOil) concentration as a base and penetration enhancer of propranolol in the cold cream preparation through rat skinmembrane in vitro. Variation concentration of VCO (0%, 14%, 28%, and 42%) was added to propanolol coldcream. Transdermal in vitro study was performed using vertical type diffusion cell with PBS pH 7,4 as receptormedia. The temperature was maintained at 35ÂºC with a constant stirring rate at 300 rpm. The transport wasconducted for 8 hours. Flux, efficiency, and lag time were calculated as responses. The results showed that flux atvarious concentration of VCO (0%, 14%, 28%, 42%) were 12,30; 14,13; 14,52; and 23,06 -1 cm-2respectively. The transport efficiency were 6,5x10-4; 7,5x10-4; 8,1x10-4; and 1,22x10-3 % cm-2 respectively. Thelag time were 1,13; 1,26; 1,11; and 0,92 hours respectively. It can be concluded that the VCO can be used mainlyas a base in the preparation of cold cream and can increase percutaneous permeation of propranolol significantly(p <0.05). VCO concentration of 42% has the highest performance.